First Record of Acanthophorus rugiceps (Colepotera: Cerambycidas) in the Root of Aegle marmelos in South West Haryana - Gaur, Ram Karan; Sharma, Sushil (Indian Forester, 2015)
Bael (Aegle marmelos Correa) is an important indigenous fruit tree of India. This medicinally important underutilized fruit is adequately rich in antioxidants and phytochemicals besides some essential nutritional components like vitamins, minerals and dietary fibres. The root borer Acanthophorus rugiceps Gahan (Coleoptera : Cerambycidae) was found associated with the roots of dried and dead bael trees. The infested roots were found packed with sawdust formed as a result of feeding by the grubs and roots were black in colour indicating association of some fungal pathogens. The mortality of bael trees was recorded to the tune of 6.6 per cent during 2012 and 5.3 per cent during 2013 in the orchard of CCS HAU Regional Research Station Bawal. The association of the soft grubs of A. rugiceps with almost all the ailing trees affirmed a definite role of the insects in the drying phenomenon.